Effect of trench width and blowing ratio on double-jet film cooling embedded in trenches. (May 2015) - Liao, Gaoliang; Wang, Xinjun; Li, Jun; Zhou, Junfei
In order to meet the problem of material damage induced by high turbine inlet temperature, reliable means of improving film cooling effectiveness are increasingly being sought by researchers involved in the study of gas turbines. Numerical investigation of the effects of trench width and blowing ratio on double-jet film cooling embedded in trench has been conducted using three-dimensional Reynolds-averaged Navier–Stokes (RANS) model. The trench is perpendicular to the mainstream flow direction. The commercial computational fluid dynamics (CFD) solver ANSYS 11.0 has been applied and shear stress transport (SST) turbulence model with gamma theta transitional model is used for turbulence model in simulations. The reliability of the numerical approach has been demonstrated by comparison of numerical results and experimental data. The blowing ratios are from 0.70 to 2.05, and the trench widths range from 5.83D to 7.92D. To investigate the film cooling effectiveness and heat transfer coefficient, the cooled surfaces have been given by adiabatic condition and fixed temperature, respectively. It is observed that the film cooling effectiveness has been greatly improved for double-jet with trench. In the vicinity region of film holes, the influence of the trench on the heat transfer coefficient is remarkable. The trench width and blowing ratio have important effects on cooling performance and heat transfer. For a given trench width, an optimum blowing ratio must be selected with an overall consideration of film cooling effectiveness and heat transfer coefficient.